Genetic Characteristics and Pathogenicity of a Novel Porcine Deltacoronavirus Southeast Asia-Like Strain Found in China - Wang, Hejie; Qin, Yibin; Zhao, Wu; Yuan, Tingting; Yang, Chunjie; Mi, Xue; Zhao, Ping; Lu, Ying; Lu, Bingxia; Chen, Zhongwei; He, Ying; Yang, Cui; et al. (Frontiers in Veterinary Science, 2021)
Farmers involved in the lucrative pork trading business between China and Southeast Asian countries should be aware of a recently discovered novel porcine deltacoronavirus (PDCoV) in Guangxi province, China. A PDCoV strain, CHN/GX/1468B/2017, was isolated from the small intestinal contents of piglets with diarrhea from this region, with a titer of 1×108.0 TCID50/mL on LLC-PK cells. The full-length genome sequence consists of 25,399 nt as determined by next-generation sequencing and this was deposited in the GenBank (accession number MN025260.1). Genomic analysis showed that CHN/GX/1468B/2017 strain had 96.9%~99.4% nucleotide homology with other 87 referenced PDCoV strains from different areas, and contained 6-nt and 9-nt deletions at positions 1733~1738 and 2804~2812, respectively, in the ORF1a gene. Phylogenetic analyses based on the whole gene sequence as well as S protein and ORF1a/1b protein sequences all showed that this strain was closely related to the Southeast Asia strain. When seven-day-old piglets were inoculated orally with the CHN/GX/1468B/2017 strain, they developed severe diarrhea, with a peak of fecal viral shedding at 4 days post-infection. Although no death or fever were observed, the CHN/GX/1468B/2017 strain produced a wide range of tissue tropism, with the main target being the intestine. Importantly, the VH:CD ratios of the jejunum and ileum in infected piglets were significantly lower than controls. These results indicate that CHN/GX/1468B/2017, isolated in China, is a novel PDCoV Southeast Asia-like strain with distinct genetic characteristics and pathogenicity. This finding enriches the international information on the genetic diversity of PDCoV.